YES Problem: a(b(b(a(x1)))) -> a(c(a(b(x1)))) a(c(x1)) -> c(c(a(x1))) c(c(c(x1))) -> b(c(b(x1))) Proof: String Reversal Processor: a(b(b(a(x1)))) -> b(a(c(a(x1)))) c(a(x1)) -> a(c(c(x1))) c(c(c(x1))) -> b(c(b(x1))) Matrix Interpretation Processor: dim=3 interpretation: [1 0 0] [c](x0) = [0 1 0]x0 [0 0 0] , [1 0 0] [b](x0) = [0 0 0]x0 [0 1 1] , [1 0 1] [0] [a](x0) = [0 0 0]x0 + [1] [0 0 1] [0] orientation: [1 0 2] [1] [1 0 1] [0] a(b(b(a(x1)))) = [0 0 0]x1 + [1] >= [0 0 0]x1 + [0] = b(a(c(a(x1)))) [0 0 1] [1] [0 0 0] [1] [1 0 1] [0] [1 0 0] [0] c(a(x1)) = [0 0 0]x1 + [1] >= [0 0 0]x1 + [1] = a(c(c(x1))) [0 0 0] [0] [0 0 0] [0] [1 0 0] [1 0 0] c(c(c(x1))) = [0 1 0]x1 >= [0 0 0]x1 = b(c(b(x1))) [0 0 0] [0 0 0] problem: c(a(x1)) -> a(c(c(x1))) c(c(c(x1))) -> b(c(b(x1))) String Reversal Processor: a(c(x1)) -> c(c(a(x1))) c(c(c(x1))) -> b(c(b(x1))) Matrix Interpretation Processor: dim=3 interpretation: [1 0 0] [1] [c](x0) = [0 0 1]x0 + [1] [0 1 0] [1], [1 0 0] [b](x0) = [0 1 0]x0 [0 0 0] , [1 1 1] [0] [a](x0) = [0 1 1]x0 + [0] [0 1 1] [1] orientation: [1 1 1] [3] [1 1 1] [2] a(c(x1)) = [0 1 1]x1 + [2] >= [0 1 1]x1 + [2] = c(c(a(x1))) [0 1 1] [3] [0 1 1] [3] [1 0 0] [3] [1 0 0] [1] c(c(c(x1))) = [0 0 1]x1 + [3] >= [0 0 0]x1 + [1] = b(c(b(x1))) [0 1 0] [3] [0 0 0] [0] problem: Qed